Mixed-Lineage Leukemia - Suci Iriani; Agus Alim Abdullah; Darwati Muhadi; Mansyur Arif (National Cancer Center - Dharmais Cancer Hospital, 2022)
Introduction: Acute Leukemia with Mixed Lineage phenotype (MLL) is leukemia that consists of cells characterized by mixed lineage markers, both from myeloid and lymphoid cells. The incidence of this leukemia is only 2-5% of all acute leukemias and is considered to have a poor prognosis.Case Presentation: A seven-year-old girl was diagnosed with MLL. The results of immunophenotyping showed two blast populations with the expressions of CD33, CD34, HLA-DR, CD117, CD13, CD19, CD10, CD20, CyMPO, Cy CD79a, and morphological features of Acute Lymphoblastic Leukemia (ALL) and Acute nonLymphocytic Leukemia (AnLL) on bone marrow aspiration. The BCR-ABL examination showed the detected BCR-ABL p210 (Major breakpoint), the majority of which was found in chronic myeloid leukemia (CML) patients. There is no definite pathogenesis of BCR-ABL p210 (MBCR-ABL) in this patient. BCR-ABL can also present in 11–29% of ALL patients but is relatively rare in childhood ALL (1%–3%) and mostly expresses p190 (minor breakpoint (mBCR-ABL)). The p210 BCR-ABL transcript is detected in 30% of adults and 20% of childhood ALL patients with Philadelphia ALL. Conclusions: MLL with BCR-ABL p210 transcript is very rare in acute leukemia. Immunophenotyping tests can detect typical MLL profiles, and WHO has standardized the diagnosis for MLL.